Business infrastructure for sustainability in developing economies - Ray, Nilanjan, 1984- (IGI Global, 2017)
"[This book] is a comprehensive reference source filled with informative discussions on the socio-economic expansion of developing nations. Featuring dynamic topics such as supply chain management, foreign trade deficits, service quality, and sustainable energy solutions, this book is an ideal resource for business managers, practitioners, professionals, and researchers who are interested in discovering the most recent trends and solutions in sustainable economic growth"- Resumé vydavatel
Keywords: ekonomický růst -- rozvojové země; infrastruktura -- rozvojové země; economic development -- developing countries; infrastructure (economics) -- developing countries; kolektivní monografie; elektronické knihy; collective monographs; electronic books